Effect of Experimental Conditions on the Sorption Efficiencies and Capacities in Removal of Fe3+ from Aqueous Solutions by Magmatic Rock Material - Lacin1, Oral; Oguz2, Ensar (Asian Journal of Chemistry, 2014)
In this manuscript, Fe3+ uptake by the particles of ignimbrite from aqueous solutions was investigated using batch sorption techniques. The sorption equilibrium studies were realised as a function of contact time, initial Fe3+ concentration, sorbent dosage, pH, temperature and agitation rate. The removal efficiency of Fe3+ and sorption capacity of the ignimbrite particles at pH 3, 293 K, 6 rps and initial Fe3+ concentration of 100 mg L-1 were 86 % and 7.1 (mg g-1), respectively. To evaluate the sorption equilibrium, four isotherm models were fitted to experimental data. The best model was determined by taking into account the correlation coefficient (R2). The best adjustment from isotherm models was observed to be the D-R (R2 0.999). The activation energy (Ea) was determined as 4.5 kJ mol-1. Thermodynamic parameters such as DH°, DS° and DG° were calculated from the slope and intercept of the linear plot of ln KD versus 1/T.